2021
DOI: 10.1007/s40262-021-01039-5
|View full text |Cite|
|
Sign up to set email alerts
|

Population Cellular Kinetics of Lisocabtagene Maraleucel, an Autologous CD19-Directed Chimeric Antigen Receptor T-Cell Product, in Patients with Relapsed/Refractory Large B-Cell Lymphoma

Abstract: Background and Objectives Lisocabtagene maraleucel (liso-cel) is a CD19-directed, defined composition, 4-1BB chimeric antigen receptor (CAR) T-cell product administered at equal target doses of CD8 + and CD4 + CAR + T cells. Large betweensubject variability has been noted with CAR T-cell therapies; patient characteristics might contribute to CAR T-cell expansion variability. We developed a population cellular kinetic model to characterize the kinetics of the liso-cel transgene, via quantitative polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…Prominent among the features that predict successful patient outcome is rapid and prolonged expansion of CAR-T cells in the first 0-90 days post infusion, measured, for example, as CAR-T AUC0-28 or AUC0-48 (10,28,29). Conversely, patients who have lower CAR-T cell expansion, for a shorter time, typically do not achieve a durable response (43)(44)(45). Increased CD19 antigen density enabled more rapid and efficient cytotoxicity with low levels of CAR-T cells relative to targeted wildtype JeKo-1 cells (Figure 2d).…”
Section: Discussionmentioning
confidence: 99%
“…Prominent among the features that predict successful patient outcome is rapid and prolonged expansion of CAR-T cells in the first 0-90 days post infusion, measured, for example, as CAR-T AUC0-28 or AUC0-48 (10,28,29). Conversely, patients who have lower CAR-T cell expansion, for a shorter time, typically do not achieve a durable response (43)(44)(45). Increased CD19 antigen density enabled more rapid and efficient cytotoxicity with low levels of CAR-T cells relative to targeted wildtype JeKo-1 cells (Figure 2d).…”
Section: Discussionmentioning
confidence: 99%
“…Blood sample collection and details of qPCR assays were described previously. 8 Flow cytometry CD3 + EGFRt + , CD4 + EGFRt + , and CD8 + EGFRt + T cells in peripheral blood were enumerated at pre-infusion and 1, 3, 7, 10, 14, 21, and 28 days and 2, 3, 6, 9, and 12 months post-infusion of liso-cel. A flow cytometry method for the assessment of CAR T cells in human peripheral blood samples was developed using fluorescently labeled cetuximab to detect EGFRt on the surface of CAR T cells.…”
Section: Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…12 Covariates considered for the models were chosen based on clinical relevance and adequate subgroup size and included age (≥ 65 vs. < 65 years), sum of the product of perpendicular diameters (SPD) per independent review committee before LDC (≥ 50 vs. < 50 cm 2 ), lactate dehydrogenase before LDC (≥ 500 vs. < 500 U/L), C-reactive protein (CRP) at baseline (≥ 20 vs. < 20 mg/L), bridging therapy (yes vs. no), prior response status (relapsed vs. refractory), and prior hematopoietic stem cell transplantation (yes vs. no). 7,8 Expansion parameters that were considered included C max and AUC 0-28 days , both of which were log 10 -transformed. For multivariable models, the expansion variable was held fixed in the model and other variables were selected from the covariates considered using a stepwise procedure with forward selection criteria P < 0.10 and backward deletion criteria P > 0.15.…”
Section: Logistic Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, CAR liso-cel possesses a non-functional receptor and is enabled to be co-expressed with the CAR receptor, and it actively binds to the CD19 marker of B-cell lymphoma. Here, they can inhibit the random proliferation of B cells' activation, and directly show the cytotoxic effect on harmful target cells [13]. A recent study from Abramson et al, 2020, showed the safety and potential activity of CAR T liso-cel for patients with large B-cell lymphomas, along with the positive aspects of liso-cel treatment, which were a low incidence of severe cytokine release syndrome and neurological problems [14].…”
Section: Introductionmentioning
confidence: 99%